2020
DOI: 10.1186/s12891-020-03287-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of avulsion fractures of the distal fibula after lateral ankle sprain in children: a diagnostic accuracy study comparing ultrasonography with radiography

Abstract: Background: The purpose of this study was to determine the diagnostic accuracy of ultrasonography for the diagnosis of avulsion fractures of the distal fibula for lateral ankle sprain in children and compare it to that of radiography. Methods: Children who sustained lateral ankle sprain were prospectively surveyed. They underwent both ultrasonography and radiography at the first clinic visit to diagnose any concomitant avulsion fractures of the distal fibula. The patients underwent follow-up radiography 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Lateral ankle avulsion fracture was reported to have a potential negative impact on postoperative rehabilitation [ 30 ], and patients with avulsion fracture should be informed of the risk of recurrent sprain and subsequent ankle instability; careful follow-up is needed for these patients [ 31 ]. Fixing or removing the avulsed fragment is determined by the size of fragment [ 32 ]; fragments can be removed for small avulsion fractures [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lateral ankle avulsion fracture was reported to have a potential negative impact on postoperative rehabilitation [ 30 ], and patients with avulsion fracture should be informed of the risk of recurrent sprain and subsequent ankle instability; careful follow-up is needed for these patients [ 31 ]. Fixing or removing the avulsed fragment is determined by the size of fragment [ 32 ]; fragments can be removed for small avulsion fractures [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the lower extremity, the calf specifically ultrasonography is a good method in diagnosing the fractures, the patients being subjected to a smaller inconvenience and less stress and also the soft tissue and muscles lesions are easier to be detected on ultrasound, these signs being suggestive for tibial fractures [29,45]. Some authors suggest that ultrasound could be used as the first-line imaging method as an alternative to conventional X-ray in the diagnosis of distal fibula fractures [47].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that POCUS is as efficient as X-ray in the diagnosis of tibia and fibula fractures in pediatric patients [46]. Takakura et al conducted a study on avulsion fractures of the distal fibula after a lateral ankle sprain, comparing the accuracy of ultrasound with conventional radiography, finding no significant differences between these two diagnostic methods, with ultrasound's sensitivity being 94% and specificity at 85% (PPV of 91% and NPV of 89%) [47].…”
Section: Us Compared With X-ray In Diagnose Of the Lower Limbmentioning
confidence: 99%
“…The sensitivity and specificity of the test were reported to be 81-100% and 85-100%, respectively. 10,26 Plantar pressure distribution was measured for 10 s in the static standing and heel-raising positions. After resynthesizing the data, the center of pressure (COP) for the left and right feet was shown in the coordinates of the posterior-anterior (P-A) and medial-lateral (M-L) components (Figure 3).…”
Section: Methodsmentioning
confidence: 99%